2014
DOI: 10.1016/j.electacta.2014.02.040
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pH on the electrocatalytic oxidation of formic acid/formate on platinum: A mechanistic study by surface-enhanced infrared spectroscopy coupled with cyclic voltammetry

Abstract: Please cite this article as: J. Joo, T. Uchida, A. Cuesta, M.T.M. Koper, M. Osawa , The effect of pH on the electrocatalytic oxidation of formic acid/formate on platinum: A mechanistic study by surface-enhanced infrared spectroscopy coupled with cyclic voltammetry, Electrochimica Acta (2014), http://dx.doi.org/10. 1016/j.electacta.2014.02.040 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
128
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(154 citation statements)
references
References 68 publications
16
128
0
10
Order By: Relevance
“…8,9,[20][21][22] However, unlike the process of CO electrooxidation reaction (E > 0.9 V), 27 the FAO is verified at potentials significantly lower (0.5 V ≤ E ≤ 0.9 V). Thus, the addition of CO in the solution where the FAO is taking place could give information about the role of CO ad on it.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…8,9,[20][21][22] However, unlike the process of CO electrooxidation reaction (E > 0.9 V), 27 the FAO is verified at potentials significantly lower (0.5 V ≤ E ≤ 0.9 V). Thus, the addition of CO in the solution where the FAO is taking place could give information about the role of CO ad on it.…”
Section: Resultsmentioning
confidence: 99%
“…15 It was found that the OCP value in the 0. solution is 0.25 V (Figure 3a). The voltammetric stripping carried out from this potential in the solution free of HCOOH (Figure 3b) shows an electrooxidation peak at 0.76 V. Both, electrochemical, 28,29 and spectroscopic, 8,9,[20][21][22] evidences indicate that this peak corresponds to the CO ad species. Thus, it is likely that in these conditions the following spontaneous dissociative adsorption is produced,…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, DLFC using formic acid has & Mônica H. M. T. Assumpção monicahelena@ufscar.br several engineering challenges such as: (i) the oxidation reactions are kinetically sluggish in acid media; (ii) the catalysts are susceptible to be poisoned and (iii) the environment of the fuel cell is corrosive [12,16]. In order to improve the use of formic acid, the use of formate in alkaline solutions has been intensely studied for fuel cell applications [3,11,[17][18][19][20]. The change from the acid media to the alkaline can dramatically improve kinetics of the oxygen reduction reaction (ORR) and also formate oxidation.…”
Section: Introductionmentioning
confidence: 99%